A unified approach based on temporal homogenisation and cycle jump for thermo-mechanical combined cycle fatigue. (February 2020) - Bhattacharyya, Mainak; Dureisseix, David; Faverjon, Beatrice
Highlights: Time homogenisation scheme is used along with cycle jump approach for simulation of combined cycle fatigue. Considerable numerical cost reduction can be achieved using the unified approach. The method is applicable for the simulation of cyclic thermo-mechanical loading. Continuum damage framework has been used to quantify the crack initiation phase of total fatigue life. Abstract: Engineering components in the aviation, automobile and locomotive sectors are often subjected to thermo-mechanical fatigue of the CCF (combined cycle fatigue) type. The fatigue behaviour for such cases can be quantified using classical continuum damage framework. The problem in such case is the immense numerical cost for a cycle-by-cycle simulation, hence a unified numerical strategy is proposed that can avoid such tedious computations for structures under CCF. Such a framework is based on temporal homogenisation and cycle jump technique that avoids cycle-by-cycle simulation for both the fast and slow cycles, providing an appreciable CPU gain with acceptable accuracy.